Picturesque Trinidad - Rice, Ben (My University, 2010)
A view of some of the houses around the Queen's Park Savannah in Port of Spain. The prominent trees on the left are palms and on the right the Saman tree with its wide canopy. Two men stand in the distance on the pitch walk of the Queen's Park Savannah.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Dwellings--Trinidad and Tobago; Savannas--Trinidad and Tobago; Palms--Trinidad and Tobago; Architecture--Trinidad and Tobago; Trees--Trinidad and Tobago; Roads--Trinidad and Tobago; Roads--Guard fences; Queen's Park Savannah (Port of Spain); Pitch Walk, The